INNV-24. THE EXPERIENCE OF FATIGUED BRAIN TUMOUR PATIENTS RECEIVING INNOVATIVE LIFESTYLE INTERVENTIONS: QUALITATIVE RESULTS FROM THE BT-LIFE RANDOMISED CONTROLLED TRIAL. (9th November 2020) - Torrens, Claire; Emerson, Julie; Hewins, William; Walker, Amie; Withington, Lisa; Mackinnon, Mairi; Robson, Sara; Dunlop, Jo; Welsh, Michelle; McBain, Catherine; Chalmers, Anthony; Grant, Robin; et al.
Abstract: BACKGROUND: Most brain tumour patients report clinically significant fatigue. Here, we aimed to explore patients' views of the experience, acceptability and usefulness of participating in a trial of novel lifestyle interventions for fatigue. METHODS: Qualitative sub-study within the 'BT-LIFE' multi-centre phase II RCT (submitted separately). Fatigued adult primary brain tumour patients in receipt of one of the trial interventions ('Health Coaching': eight coaching sessions targeting lifestyle behaviours; plus or minus 'Activation Coaching': two additional interviews targeting motivation to change) took part in a semi-structured interview following completion of the interventions. A realist approach to the 'framework' method was used to analyse verbatim transcripts, with inductive and deductive codes assigned to the realist domains of Context-Mechanism-Outcome. RESULTS: Twenty themes and 53 sub-themes were derived from the data. Patients' (n= 21) understanding of and engagement with the interventions were influenced by their expectations, attitudes to life, and experience of living with a brain tumour. Behaviour change was supported by goal-setting, monitoring using a weekly diary, the motivational 'push' by coaches, and family/ social support where available. Barriers to engagement included technical diary difficulties, time limitations including work and holiday schedules, and interference from life events. Most patients described beneficial changes in health behaviours, self-efficacy, and general health and wellbeing. About half indicated actual improvement in fatigue levels; others reported no direct change but they could now cope better with fatigue. A minority experienced no change or worsening fatigue. CONCLUSION: Most fatigued brain tumour patients were able to make positive changes after lifestyle coaching, despite physical and cognitive impairments. However, their experiences were varied. Those for whom the interventions were a good 'fit' with their pre-existing outlook, lifestyle, and physical and emotional capabilities, appeared to achieve most benefit. These qualitative findings will inform further work addressing the disabling symptom of brain tumour-related fatigue.